Amplification of a complete genomic sequence of pal gene from sago palm - Emmalene, Kunbun (Universiti Malaysia Sarawak (UNIMAS), 2015)
Metroxylon sagu or sago palm is a versatile underutilized plant which able to withstand various biotic and abiotic stresses such as pathogen, heat and especially waterlogging. Various evidences state that phenylalanine ammonia lyase (PAL) is the key enzyme that contributes to this versatility. PAL in this plant is responsible for the biosynthesis of lignin and salicylic acid, which is essential for plant systemic acquired resistance (SAR) and defence against pathogen attack respectively. PAL genomic DNA of sago palm was isolated and PCR was conducted to amplify the full-length PAL genomic DNA. First primers produced ~2,500 bp amplicons whereas another pair of primers generated ~ 1,200 bp amplicons. These amplicons were sequenced and analysed to be 1,111 bp and 1,125 bp long, respectively. BLASTn was conducted to determine the sequence homology of msPAL genomic DNA with known sequences available in GenBank. Homology searching showed that the amplified fragment had high sequence homology with Cinnamomum osmophloeum by showing 98% similarity.